Improving biogeochemical knowledge through technological innovation. Issue 1 (1st February 2011) - Melack, John M; Finzi, Adrien C; Siegel, David; MacIntyre, Sally; Nelson, Craig E; Aufdenkampe, Anthony K; Pace, Michael L
Abstract : The understanding of biogeochemical cycles has benefited from technological advances facilitating new kinds of measurements and observations. Satellite‐borne ocean‐color sensors that assess the physiological status of phytoplankton have led to improved estimates of oceanic productivity, as have micrometeorological approaches measuring terrestrial photosynthesis and respiration. The advent of satellites fitted with synthetic aperture radar (a specialized sensor used to determine inundation extent and vegetation types in wetlands) has revealed large fluxes of carbon dioxide and methane from these areas. Advances in the measurement of chemical constituents and turbulence have allowed the detection of high‐resolution coupling between physical and biogeochemical processes. Genomics and proteomics – the study of genes and of an organism's complement of proteins, respectively – have revolutionized our understanding of the types of cells present in the environment and their ability to transform elements by allowing direct assessment of gene and protein sequences.